Two‑step drying of soya bean seed germplasm often improves subsequent storage longevity - Salvador, O.F.; Ellis, R.; Oyatomi, O.; Abberton, M.; Hay, F.R. (2025)
It is recommended that seeds for genebank storage are dried to low moisture content at 10–25 °C, 10–15% RH, but in some crops, an initial warmer drying temperature may provide better longevity. Seeds of diverse accessions of soyabean (Glycine max (L.) Merr.) produced in three seasons and harvested shortly before or at harvest maturity were initially dried at 17, 30 or 40 °C with 15% RH and subsequently at 17 °C with 15% RH; seeds were fumigated either before or after initial drying. Seed longevity in hermetic storage at 45 °C with approximately 9% moisture content was affected by the initial drying treatments, but effects varied among treatment combinations and accessions. Seeds harvested before harvest maturity, at 10–14% moisture content, tended to benefit from warmer temperature drying. Fumigation before initial drying resulted in shorter longevity than fumigation afterwards for about 70% of harvested seed lots. Most treatment combinations across all experiments showed seed longevity was improved, often considerably, by 4 days’ initial drying at 40 °C compared to drying at 17 °C throughout. Longevity was also improved in many treatment combinations (fewer than at 40 °C) by initial drying at 30 °C compared to 17 °C. In a minority of treatment combinations, seed longevity was reduced by drying at 40 or 30 °C compared to 17 °C. The research shows a potential benefit to subsequent seed longevity from initially drying soya bean seeds at 40 °C, rather than 10–25 °C, for most accessions, particularly those harvested early; this benefit may have been due to greater post-harvest maturation in the warmest regime.